High temperature ferromagnetism in dilute ferromagnetic oxides - COEY, JOHN MICHAEL DAVID (My University, 2005)
High temperature ferromagnetism in thin films of dilute magnetic oxides is a widespread phenomenon, of which there appear to be two sources. One is the contribution of the 3d dopant ions themselves, the other is related to crystal defects in the interface region. The latter contributes a magnetic moment of 100?400??B per square nanometer of substrate area, which is largely independent of film thickness or dopant concentration. It is suggested that the defects are two-electron or two-hole centers which have a spin triplet as ground state or low-lying excited state. HfO2, an example of the former, is ferromagnetic even when undoped. In ZnO or SnO2, examples of the latter, the magnetic dopant may stabilize the spin triplet by exchange.
PUBLISHED
Keywords: Physics